The mining reform of the 1990s in Brazil: An analysis in light of the World Bank's Mining Strategy for Latin America and the Caribbean (Huellas, 2024)
The aim of this article is to identify and analyze the norms that altered the legal framework of the Brazilian mining sector during the 1990s, which were based on the World Bank Mining Strategy for Latin America and the Caribbean in 1997. To that end, general characteristics of the mining sector are described, in particular iron ore production and the role of the Vale do Rio Doce Company. Consideration is also given to the conditions leading up to the reform, especially the clashes between the National Coordination of Geologists (CONAGE) and the Brazilian Institute of Mining (IBRAM) during the National Constituent Assembly of 1987. Then, the norms that reformed mining regulations are analyzed, with special attention to the political, economic and environmental consequences of the interaction between norms and state omissions. It is argued that despite not being announced as such, a mining reform was enacted in Brazil in the 1990s, which effectively produced a transformation of the legal framework of this activity as part of a broader homogenization of mining sector regulations on a global scale.
Keywords: Mining; Brazil; World Bank; Mining Sector Reform